2019
DOI: 10.1021/acsbiomaterials.9b00858
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed β-Tricalcium Phosphate Scaffold Combined with a Pulse Electromagnetic Field Promotes the Repair of Skull Defects in Rats

Abstract: Trauma, infection, cancer, and congenital diseases can lead to bone defects. The combination of 3D printing with biomaterials is of great significance in the treatment of bone defects. In addition, pulse electromagnetic fields (PEMFs) can promote bone regeneration. The main purpose of this study was to evaluate the effects of 3D-printed scaffolds using β-tricalcium phosphate (β-TCP) as the raw material combined with a PEMF on the proliferation and differentiation of rat adipose stem cells (rADSCs) and on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Bone is a complex tissue and has a variety of physiological functions, including providing mechanical strength for locomotion, supporting soft tissues, hosting bone marrow, and protecting internal organs, which are mainly attributed to its hierarchical structures assembled by hydroxyapatite nanocrystals, collagenous proteins, cells, and many other biomolecules. Bone defects caused by trauma, infection, fracture, congenital diseases, and tumor have placed an increasing demand for bone grafts in recent years. Nowadays, over 2 million bone grafting procedures have been performed annually worldwide, and the demands are still increasing. Typical treatments using bone tissue from patients (i.e., autografts) or human donors (i.e., allografts) as bone grafts face huge limitations. For example, autologous bone grafts are limited by the lack of adequate donor tissues, the morbidity of donor site, and the postoperative complications, while allografts suffer from issues such as immune rejection and disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Bone is a complex tissue and has a variety of physiological functions, including providing mechanical strength for locomotion, supporting soft tissues, hosting bone marrow, and protecting internal organs, which are mainly attributed to its hierarchical structures assembled by hydroxyapatite nanocrystals, collagenous proteins, cells, and many other biomolecules. Bone defects caused by trauma, infection, fracture, congenital diseases, and tumor have placed an increasing demand for bone grafts in recent years. Nowadays, over 2 million bone grafting procedures have been performed annually worldwide, and the demands are still increasing. Typical treatments using bone tissue from patients (i.e., autografts) or human donors (i.e., allografts) as bone grafts face huge limitations. For example, autologous bone grafts are limited by the lack of adequate donor tissues, the morbidity of donor site, and the postoperative complications, while allografts suffer from issues such as immune rejection and disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The skull defect of patients has a personalised shape and repairing it with mass-produced scaffolds is difficult. Three-dimensional printing processing technology brings a new direction for the preparation of personalised scaffolds of skull defects based on patient CT data [ 59 ]. According to different principles, 3D printing can be divided into fused deposition modelling (FDM) [ 60 ], stereo lithography appearance (SLA) [ 61 ], selective laser sintering (SLS) [ 62 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…And they pointed out that such a combination of EMFs and magnetic HAp microspheres would be a new therapeutic strategy to meet clinical needs in bone cement and scaffolds for local bone replacements [ 139 ]. β-tricalcium phosphate(β-TCP) is an osteoinductive ceramic that can combine with EMFs to treat rat skull defects [ 140 ]. It is reported that iron-doped β-TCP significantly upregulates ALP expression and calcium deposition when an external PEMF was applied [ 141 ], which implies that a combination of EMFs and iron-doped bioceramics may be a new method for bone regeneration.…”
Section: Emfs’ Applications In Assisting Bone Tissue Engineeringmentioning
confidence: 99%